Charting Equality: Women's Rights and Inheritance Law Reform - Hidayati, Nuzulia Febri; Andriyati, Nofica; Billah, Mu’tashim (Sawwa: Jurnal Studi Gender, 2024)
The discussions around inheritance law highlight differences in quantity, potentially leading to discrimination claims without fully considering the legal rationale. The study explores how women can assert equality within diverse legal frameworks shaped by cultural contexts. This study using qualitative methods and case studies gather data to understand how women have developed unique legal cultures and sub-cultures. Findings suggest that women can advocate for gender justice within varying legal constitutions as long as they ensure protective measures are in place. Ultimately, for inheritance law to remain relevant and equitable, it must accommodate women’s perspectives and provide a foundation that respects their rights, ensuring that the law serves society fairly and inclusively without marginalizing any group.